Implementasi Financial Parenting dengan Metode Smart untuk Anak Usia Dini - Ni Ketut Sriwinarti; Khairunnisa Khairunnisa; Defel Septian; R. Ayu Ida Aryani (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This consumptive behavior makes teenagers always want to consume good excessively and unreasonably. “Bina Sekolah” is a community service activity that is routinely carried out every semester under the auspices of the Accounting Study Program Bumigora University. This program aims to introduce the meaning of money and save money by saving so that it can be used for more productive purpose the children are invited to learn to manage personal money, have financial planning, appreciate money, learn discipline and make pride. The student are introduced to saving with the SMART method which stand for Specific, Measurable, Achievable, Relevant, and Time-bound. So that it becomes a challenge for them and makes saving activities interesting. This community service activity was carried out at SDN 1 Sedau, where participants in this activity involved approximately 30 students. The method of implementing this socialization is divided into several stages, namely coordination, media preparation, material socialization, discussion and games and giving souvernirs. The socialization material provided is in the form of the history of saving, why save, what banks are in Indonesia, and finally making a saving target. The material is packaged with interactive videos so that children can be enthusiastic in following all activities. This activity went well and lively because it was accompanied by students who guided the activities while playing games. The knowledge gained in this service is expected to provide ongoing motivation to children to continue saving and so that the agreed targets can be achieved